Karakterisasi dan Pemilihan Alat Pengendali Limbah Sandblasting di Bengkel Blasting Industri Konstruksi Kapal - Ahmad Erlan Afiuddin; Ragil Zika Hibriza; Dwi Ratri Mitha Isnadina (Al-Ard: Jurnal Teknik Lingkungan, 2019)
Sandblasting waste from the blasting process of ship construction has a high potential to pollute the air and a negative impact to the environment or human health. Nowadays the sandblasting waste from the blasting process of the ship construction industry has not been well managed, Therefore, it is necessary to characterize sandblasting waste and to select and apply an appropriate sandblasting waste control device. Tests was carried out by taking particulate samples in the site with High Volume Air Sampler (HVAS) equipment followed by the Gravimetric method, Scanning Electron Microscopy (SEM) and Atomic Absorbtion Spectrophotometry (AAS). The gravimetric method was used to test the concentration of sandblasting waste with an average yield of 6,654.545 mg/m3. The particulate size obtained from SEM testing was 1.751 to 63.03 µm, testing with the AAS method to get the value of heavy metal content of Fe and Al on average of 1.6375 mg/m3 and 2.2925 mg/m3. Control technology that can use for sandblasting waste are Gravity Settling Chamber or Cyclone for preremoval and Bag Filter or Scrubber or Electrostatic Precipitator as an advance removal.Keywords: ships construction, Sandblasting and Particulate control technology